Misselling through Agents - Inderst, Roman; Ottaviani, Marco (American Economic Review, 2009)
This paper analyzes the implications of the inherent conflict between two tasks performed by direct marketing agents: prospecting for customers and advising on the product's “suitability” for the specific needs of customers. When structuring salesforce compensation, firms trade off the expected losses from “misselling” unsuitable products with the agency costs of providing marketing incentives. We characterize how the equilibrium amount of misselling (and thus the scope of policy intervention) depends on features of the agency problem including: the internal organization of a firm's sales process, the transparency of its commission structure, and the steepness of its agents' sales incentives. (JEL M31, M37, M52)